Inovasi Metode Pembelajaran - Hazrati Ashel; Riandi Riandi (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2022)
Physics is a subject that consists of concepts related to real life. Empirical phenomena can be observed directly through experimental activities. However, this experimental method is still not optimally applied by teachers in learning. Problems that can be an obstacle in carrying out experiments in schools include difficulties in collecting and analyzing data on some Physics materials, not all schools have adequate practicum tools, and it is difficult to carry out experimental activities in online learning conditions. Based on this, a mixed-methods research was carried out to find a solution to this problem. Qualitative research consisting of literature review about real experimental methods, virtual experimental methods, and the use of video analysis software in physics learning was conducted to obtained innovation on experimental methods. Furthermore, quantitative research was conducted to determine the difference of student’s conceptual understanding before and after being given the intervention. Based on the results of the literature review, it is concluded that the experimental method innovation that can be carried out is the mixed experimental method by combining real and virtual experimental activities. One example of technology that can be used in this method is video analysis software. The results of data analysis showed that there was a difference in concept understanding between before and after given the mixed experimental method. Therefore, the innovation of the learning method can improve students' understanding of concepts in learning Physics.